Strategy Recruitment and Selection Employee Bank in Facing Digital Transformation - Junarta, Harbyanto; Ma’ruf Alqifari, Sulaeman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Digital transformation has significantly changed the banking industry landscape, driving the need for a workforce with high digital skills and adaptability. This research aims to analyze strategy recruitment And selection HR Which effective for banking in digital era. The methods used is a study literature systematic (systematic literature review) by analyzing various articles, journals, and reports related to HR management, digital recruitment, and the banking industry. Research shows that banks need to adopt digital-based recruitment strategies that leverage online platforms, social media, and artificial intelligence (AI) to reach relevant talent. Selection processes should also be updated by utilizing online tests, data analytics, and competency-based interviews to identify candidates who possess not only technical expertise but also problem-solving and innovation capabilities. In conclusion, banks that are able to align their recruitment and selection strategies with the demands of the workforce will excel. digital will more competitive And sustainable in the face of change The recommendations include investing in recruitment technology and training HR teams to master new assessment methods.